2009
DOI: 10.1210/jc.2008-2269
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Telomere Length and Telomerase Activity with Occult Ovarian Insufficiency

Abstract: Aberrant telomere homeostasis is associated with occult ovarian insufficiency in young women. This finding is consistent with the presence of telomeric attenuation that has been shown in multiple age-related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 65 publications
2
84
0
1
Order By: Relevance
“…Human tissues often display age-dependent telomere shortening (Keefe & Liu 2009, Takubo et al 2010. A lack of GC TA has been found to be associated with occult ovarian insufficiency (Butts et al 2009). Our previous study suggested that patients with higher levels of TA in the GCs had a greater likelihood of becoming pregnant than those with less TA.…”
Section: Discussionmentioning
confidence: 99%
“…Human tissues often display age-dependent telomere shortening (Keefe & Liu 2009, Takubo et al 2010. A lack of GC TA has been found to be associated with occult ovarian insufficiency (Butts et al 2009). Our previous study suggested that patients with higher levels of TA in the GCs had a greater likelihood of becoming pregnant than those with less TA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was showed that the relative telomere length was longer in GCs from mature oocytes compared with GCs from immature oocytes in human [12]. In addition, the abnormal telomere lengths in GCs were confirmed to be related to the female infertility and diminished ovarian reserve [10]. It was shown that luteinized human GCs have a certain potential for proliferation and that telomerase activity of luteinized GCs may predict the clinical outcomes of in vitro fertilization [11].…”
Section: Telomerase Activity and Stemness In Granulosa Cellsmentioning
confidence: 96%
“…Hence, it is highly likely for ovarian somatic cells (granulosa and theca cells) to also undergo cellular senescence. Short telomeres and low telomerase activity in granulosa cells are observed in women (≤37 years old) with diminished ovarian reserve (Butts et al 2009). In humans, shortened telomere length in cumulus cells, which are specialized granulosa cells, is associated with the development of poor embryos (Cheng et al 2013).…”
Section: Cellular Senescence and Ovarian Agingmentioning
confidence: 99%